2019
DOI: 10.1093/nsr/nwz019
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of nitric acid from air and ammonia through waste utilization

Abstract: Commercial nitric acid (HNO3) and ammonia (NH3) are mostly produced through the Ostwald process and the Haber-Bosch process, respectively. However, high energy demand and enormous greenhouse gas accompy these processes. The development of economical and green ways to synthesize HNO3 and NH3 is highly desirable for solving the global energy and environmental crisis. Here, we present two energy-efficient and environmentally friendly strategies to synthesize HNO3 and NH3 at distributed sources, including the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
233
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(238 citation statements)
references
References 42 publications
2
233
1
2
Order By: Relevance
“…The in situ transformation of the catalyst in the OER process has been widely reported. [36] Yanmei Shi et al reported that tannin-NiFe is converted into Ni x Fe 1-x O y H z in the OER process, as the final OER catalyst, and shows excellent OER catalytic performance. [37] This inference can be further confirmed by the characteristic peaks of O 1s XPS spectrum (CoÀ O and Co-OH).…”
Section: Resultsmentioning
confidence: 99%
“…The in situ transformation of the catalyst in the OER process has been widely reported. [36] Yanmei Shi et al reported that tannin-NiFe is converted into Ni x Fe 1-x O y H z in the OER process, as the final OER catalyst, and shows excellent OER catalytic performance. [37] This inference can be further confirmed by the characteristic peaks of O 1s XPS spectrum (CoÀ O and Co-OH).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, a strategy of electrocatalytic nitrate reduction into ammonia was developed . Notably, this technique could be easily incorporated into an existing technological process to produce value‐added ammonium/ammonia and clean water (Supporting Information, Figure S1).…”
Section: Figurementioning
confidence: 99%
“…[28] In this regard, a strategy of electrocatalytic nitrate reduction into ammonia was developed. [29] Notably, this technique could be easily incorporated into an existing technological process to produce value-added ammonium/ ammonia and clean water (Supporting Information, Figure S1). However, the selectivity and Faradaic efficiency of this process were relatively low because of the complicated eight-electron reduction course from nitrate to ammonia and the competitive hydrogen evolution reaction.…”
mentioning
confidence: 99%
“…These steps involve processes requiring high temperature and high pressure, resulting in high‐energy consumption and large amounts of carbon dioxide emission. However, despite the great practical value to replace Ostwald process, direct nitrogen oxidation reaction (NOR) under mild conditions remains largely unexplored . Electrochemical techniques have been widely employed in the synthesis of value‐added products, owing to the feasibility of non‐thermal activation initiated by the applied potential .…”
Section: Figurementioning
confidence: 99%